Analyzing Operational Sustainability of Organization - E. A. Tikhomirov (Вестник Российского экономического университета имени Г. В. Плеханова, 2020)
The article studies strategic and operational sustainability of organization and provides methodological approach to analyzing of company business sustainability. The author introduces index of business sustainability, which allows us to monitor operational sustainability of organizations on the basis of income and product (service) cost. Methodology of calculating the index of business sustainability with the help of data given in Form P-5 (m) of statistic reporting was provided. On the basis of business sustainability index its flexibility can be analyzed as the correlation of business sustainability index of the current and previous periods. It is shown that in case this correlation exceeds 1, sustainability of enterprise development rises, if it is 1, then sustainability of enterprise development maintains and if it is lower than 1, sustainability of enterprise development drops and managerial solutions are required to raise sustainability of enterprise development. At the same time factors affecting business sustainability were identified, including the remuneration fund, which should be retained and increased in case of other cost optimization.